Life Cycle Analysis Of Fish Products Emphasis On Fish Wastes As Raw Material For Bioplastics - Jong, Cheng Kiat (Universiti Sains Malaysia, 2017)
The objectives of this research were to classify the wastes generated during the manufacturing processes of fish products and evaluate the environmental impacts of the fish wastes through life cycle analysis (LCA) as well as to characterize the potential utilization of fish wastes as protein-based thermoplastics. Production of canned fish products from Protigam Food Industries Sdn. Bhd. was investigated by following four steps in LCA; (1) goal and scope definition, (2) life cycle inventory (LCI) analysis, (3) life cycle impact assessment (LCIA) and (4) interpretation of result. The goal of this work is ‘cradle-to-grave’ life cycle of canned fish products whereas the scope is the functional unit of every 1 tonne of raw fish entering the factory. The LCI analysis was carried out by obtaining the inventory data of the whole process flow as well as the inputs and outputs of each subsystem in the manufacturing process. Then, LCIA was performed by identifying the related impact categories for the canned fish products, followed by calculation of the values for those related impact categories. The values were then normalized with the functional unit. It was shown that for every 1 tonne of raw fish entering the factory, about 0.22 tonnes of municipal solid waste was produced, an increase of 1.27 kg eq PO4 in eutrophication potential and 1383.6 kWh of electricity was consumed. Lastly, the results were interpreted through contribution analysis where the process of butchering, icing and retorting were identified as the biggest contributor for impact categories of municipal solid wastes, eutrophication potential and energy consumption respectively. On the other hand, the result of Kjeldahl analysis showed that fish waste powder has about 16% protein content, making it a suitable candidate for protein based thermoplastics.